What Does Digital Learning Teach? - Shulga, Marina (International Journal of Interactive Mobile Technologies (iJIM), 2023)
Digital learning does not determine its strategic benchmarks independently since it always represents only a training system component. Consequently, its goals and objectives cannot be understood without a preliminary understanding of the purposes and objectives put forward by the training system a part of which it forms. The issue of identifying this purpose as a person being a cognitive activity subject or a person being a bearer of a certain number of skills requires clarification. The digital learning concept will always contain a positive ("correct") or negative ("incorrect") answer to this question in the "default" status, as prescribed by the training system. And it will serve as an auxiliary tool only in promoting (and approving) different concepts of human capacity as a "correct" one.